Replication Data for: \"Divided Attitudes Toward Rectifying Injustice: How Preferences for Indigenous Policies Differ Between the Indigenous and Majority Populations of Norway and Sweden\" - Bergmann, Fabian (Harvard Dataverse, 2023)
This is the replication material for the analysis presented in the article \"Divided Attitudes Toward Rectifying Injustice: How Preferences for Indigenous Policies Differ Between the Indigenous and Majority Populations of Norway and Sweden\". The data is a subset of the Nordic Peoples Survey dataset by Holzinger et al. (2023). Holzinger, Katharina, Tanja Kupisch, Fabian Bergmann, Anika Lloyd-Smith, Sven-Patrick Schmid, Rusen and Yasar. 2023. \"Nordic Peoples Survey.\" Harvard Dataverse, V1, https://doi.org/10.7910/DVN/F6TSFG